Efficacy and Safety of Shenqu Xiaoshi Oral Liquid Compared With Domperidone Syrup in Children With Functional Dyspepsia - Yu, Yi; Xie, Xiao-Li; Wu, Jie; Li, Zhong-Yue; He, Zhi-Gang; Liang, Chun-Jie; Jin, Zhong-Qin; Wang, Ai-Zhen; Gu, Jian; Huang, Ying; Mei, Hong; Shi, Wei; et al. (Frontiers in Pharmacology, 2022)
BACKGROUND Treatment of functional dyspepsia (FD) in children is generally symptomatic and unsatisfactory. Traditional Chinese medicines, such as Shenqu Xiaoshi Oral Liquid (SXOL), have been recommended to alleviate dyspeptic symptoms. However, evidence of their safety and efficacy remains limited to date. AIM To assess whether 2 weeks of therapy with SXOL was non-inferior to domperidone syrup in children with FD. METHODS In this randomized, double-blind, double-simulated, non-inferiority, multi-center clinical trial, we recruited children (3–14 years) with FD according to the Rome IV criteria from 17 tertiary medical centers across China. Patients were randomly allocated (1:1) to receive SXOL or domperidone syrup for 2 weeks. We compared the participants’ clinical scores from both groups based on the severity and frequency of dyspepsia symptoms according to Rome IV criteria (0, 1, 2, and 4 weeks after randomization). The primary endpoint was the total response rate, which was defined as the proportion of patients with a decrease of 30% or more in the FD symptoms clinical score from baseline, at the end of the 2-week treatment. A non-inferiority margin of -10% was set. Secondary endpoints and adverse events were assessed. This trial is registered with Chictr.org.cn, number ChiCTR1900022654. RESULTS Between February 2019 and March 2021, a total of 373 patients were assessed for eligibility, and 356 patients were enrolled and randomized. The clinical response rate at week 2 was similar for SXOL (118 [83.10%] of 142) and domperidone (128[81.01%] of 158); difference 2.09; 95% CI -6.74 to 10.71, thereby establishing non-inferiority. The total FD symptom scores were significantly improved in the two groups at 1-, 2-, and 4-week follow-up periods (P < 0.005). The decrease in symptom score compared with the baseline were similar between these two groups. Over the total study period, 10 patients experienced at least one treatment-related adverse event (six [3.37%] in the SXOL group, four [(2.25%] in the domperidone group), although no serious adverse event was noted. CONCLUSION Treatment with SXOL effectively improves dyspeptic symptoms and is well tolerated. In addition, it is not inferior to domperidone syrup and leads to sustained improvement in Chinese children with FD.